Ushuluddin dan Globalisasi: Menyongsong Masa Depan dengan Harapan - Syaifan Nur (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2014)
Globalization has been the biggest influence in human life in all areas. Therefore, it becomes a challenge to adapt to the global world with no identity left as the Islamic Higher Education (IHE). In fact, Islamic Theology Department aspart of the IHE must beable to adapt quickly to the global world, in order not to befar be hind in education that has been evolved. Settling in all aspectsof course veryi mportant in order to face the future withthe expectance. The Experience of Islamic State (UIN) Sunan Kalijaga shown how the IHE included as the Department of Islamic Theology had done the alignment with the global world.